Common soccer injuries. Diagnosis, treatment and rehabilitation - Tucker, A. M. (Sports Medicine, 1997)
Soccer is a game with worldwide appeal. Increasing numbers of participants are members of all age groups and skill levels. The game presents to the sports medicine practitioner a wide variety of musculoskeletal and medical problems. Soccer injuries increase in frequency as the age of participant increases, with a low incidence of injury in preadolescent players. Musculoskeletal injuries most commonly affect the lower extremities and include contusions, acute and chronic musculotendinous strains, and ligamentous injuries to the knee and ankle. Most injuries are minor and respond to analgesics, therapy modalities and exercise therapy. Groin pain is a common problem and particularly prevalent among soccer players owing to the game's specific stresses. Other less common but important injuries include facial trauma, mild brain injury (concussion) and heat-related injury. Team physicians, athletic trainers and physical therapists need to possess a basic understanding of the most common injuries and problems in order to maximise safe participation for their athletes.